2007
DOI: 10.1186/1471-2407-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-3 over-expression enhances tumourigenesis in MCF-7 and MDA-MB-231 breast cancer cell lines: involvement of the IGF-1 signalling pathway

Abstract: Background: Stromelysin-3 (ST-3) is over-expressed in the majority of human carcinomas including breast carcinoma. Due to its known effect in promoting tumour formation, but its impeding effect on metastasis, a dual role of ST-3 in tumour progression, depending on the cellular grade of dedifferentiation, was hypothesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
(39 reference statements)
1
32
0
Order By: Relevance
“…For this we used the BR55 MB targeted against the human VEGFR2 which different from most previous approaches [11,12,[14][15][16][17]22]. Most importantly, the coupling of VEGFR2-targeting ligands to the MB was not performed via the potentially immunogenic streptavidin-biotin method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this we used the BR55 MB targeted against the human VEGFR2 which different from most previous approaches [11,12,[14][15][16][17]22]. Most importantly, the coupling of VEGFR2-targeting ligands to the MB was not performed via the potentially immunogenic streptavidin-biotin method.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this study was to investigate the circulation characteristics of novel nonspecific microbubbles (BR38) and of VEGFR2-targeted (BR55) microbubbles (MB), both suited to clinical use. Furthermore, their ability to discriminate differences in the angiogenesis of oestrogenindependent, highly aggressive (MDA-MB-231) and oestrogen-dependent, low aggressive (MCF-7) breast cancer xenografts [20][21][22], respectively, was evaluated. With BR38 we assessed the vascularization as an angiogenic marker and with BR55 the VEGFR2-status.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anthocyanin intake inhibits tumor proliferation in patients with colorectal cancer (6,10). Studies have also indicated that various anthocyanins derived from fruits and vegetables are effective in the prevention or reduction of solid tumor development in animal models (11)(12)(13). Altogether, these data indicate that using dietary chemopreventive ONCOLOGY REPORTS 24: 1471-1477 Anthocyanins are novel AMPK·1 stimulators that suppress tumor growth by inhibiting mTOR phosphorylation agents, such as AIMs, might be a promising strategy for controlling colon cancer.…”
Section: Introductionmentioning
confidence: 89%
“…IGF-I signaling can promote the tumor growth and invasion through regulation of PCNA and VEGF expression (33,34). Furthermore, MMP II leads to the stimulation ofthe IGF-I R pathway in carcinoma cells, thus enhancing their proliferative capacity (30,35). In the present study, our finding showed that knockdown ofMMP II downregulated the expression ofIGF-I, PCNA and VEGF and suppressed the bioactivities in GAC cells, suggesting that MMPII may be involved in the development and progression of gastric cancer via IGF-I-mediated regulation of the PCNA and VEGF expression.In conclusion, our findings demonstrate that MMP II expression is increased in human GAC tissues, but does not correlate with the clinicopathologic features.…”
Section: Discussionmentioning
confidence: 99%